Comparing the kinetics of the hydrolysis of by-product from channel catfish (Ictalurus punctatus) fillet processing by eight proteases. (August 2019) - Tan, Yuqing; Chang, Sam K.C.; Meng, Shi
Abstract: Channel catfish farming is the most important warm water aquaculture in the United States and is very important to the rural economy. This study's objective was to investigate the kinetics of the enzymatic hydrolysis of catfish by-product. Channel catfish ( Ictalurus punctatus ) by-products (heads and frames) were collected from local catfish processing plant. Papain, ficin, bromelain, neutrase, alcalase, protamex, novo-proD and thermolysin were used for hydrolysis. Proteolytic activities of those proteases were examined at different hydrolysis temperature, proteases cost for reaching certain degree of hydrolysis was predicted. Degree of hydrolysis (DH) of the hydrolysates and hydrolysis kinetics were studied. Emulsifying and foaming property and stability of selected hydrolysates were evaluated. Results indicated that thermolysin had the highest activity (8.2 × 10 8 Azocoll U/g and 5.6 × 10 6 Azocasein U/g) at 70 °C. The highest DH of the hydrolysates were observed in 120 min with the concentration of 80 AzU/g for all enzymes. Ficin (80 AzU/g) was the most efficient in hydrolyzing the by-product (DH reaching 71%) in 120  min at 30 °C. The hydrolysis curves fit the Peleg model well with R 2 higher than 0.91. This study provides important engineering information for choosing proteases and processing conditions for optimization of efficiency, yield and economy. Highlights: Channel catfish processing by-product was hydrolyzed by 8 proteases. Protease reaction kinetics showed ficin was the most efficient to hydrolyze catfish proteins. Proteins and peptide pattern changes upon hydrolysis were quantitated by electrophoresis. Thermolysin showed the least costly to reach a certain DH level as predicted according to the kinetic models.